Integrating Islamic spirituality into management control systems: A case study of sharia-based leadership - Tatik, Tatik; Falikhatun, Falikhatun (JIFA (Journal of Islamic Finance and Accounting), 2024)
This study aims to explore the practice of Management Control Systems (MCS) rooted in Islamic spiritual values. Utilizing an interpretive qualitative method with a single case study approach, data were collected through interviews, observations, and document analysis. The analysis of MCS was guided by principles derived from Islamic spirituality. The findings reveal that the spiritual values of the leaders, deeply influenced by the Al-Qur'an, Shiroh Nabawi, and their engagement with various Islamic communities, foster spiritual maturity. This spiritual foundation shapes wise leadership and results in an MCS that effectively steers the organization towards its intended goals. The implications of this research suggest that Muslim leaders should integrate Islamic character into the design of MCS, ensuring that organizations operate effectively to achieve both worldly and spiritual objectives, ultimately contributing to the well-being of the broader universe. The novelty of this study lies in its provision of new insights into the expression of MCS practices based on Islamic spirituality, the development of Islamic leadership character, and the connection between MCS and Sharia-compliant agreements.